Ethnomethodology Study of Digitalized Social Communication Apprehension in Basmala Youth Community Members - Tuti Widiastuti (Ikatan Sarjana Komunikasi Indonesia, 2020)
In the era of Society 5.0, the role of communication technology was further enhanced so that it made it easier for humans in various aspects, such as economic, social, cultural, educational, health, business, and so on. However, the sophistication of information and communication technology causes interpersonal to interact less rarely face to face and face to face because it is more comfortable interacting through cyberspace through social media. This research was conducted to illustrate how social communication from understanding anxiety in the digital age. In conducting interactions, each individual can experience communication fears where individuals tend to experience anxiety because too much information is received. The group can be one of the very positive spheres of communication. The object of this research is Basmala members, who have various backgrounds as members of Islamic spiritual groups who uphold religious values. This research uses a qualitative research method with an ethnomethodology type that looks at how the disclosure of reality in people's lives and how individuals receive, learn, apply information provided in the community. Basmala is an Islamic spiritual organization whose members are students. As a religious organization where the culture and activities of the organization also have characteristics that can lead to the basic rules of religion that are expected to familiarize its members to deal with differences in the communication process to overcome the causes of communication apprehension